Perfecting China’s anti-monopoly legal system: international shipping in the digital economy era - Shi, Yuanhong (Frontiers in Marine Science, 2024)
The rapid development of digital economy promotes the transformation and upgrading of China’s shipping fields. Among them, the international shipping anti-monopoly legal system is one of the important contents of China’s shipping legislation. In the era of digital economy, it is difficult for the existing system to better regulate the international liner shipping market with shipping alliance as the core. Countries have re-examined the anti-monopoly legal regulation system of international shipping. As both a major shipping and trading country, it is urgent for China to improve its shipping legislation with the anti-monopoly system as its core. In order to cope with the new pattern of shipping alliance in the era of digital economy, we should learn from the advanced experience of international shipping legislation, base on the perspective of China’s shipping economic development and our own needs, and make effective exploration from the aspects of coordinating the development of digital economy and shipping management mechanism, improving shipping supervision ability and accelerating the improvement of shipping legal system with Chinese Characteristics.